A familial case of B‐cell expansion with NF‐κB and T‐cell anergy caused by a G123D heterozygous missense mutation in the CARD11 gene. Issue 12 (21st September 2022) - Takase, Yusuke; Tanioka, Shinji; Ishimura, Masataka; Yoshiura, Koh‐ichiro; Mori, Yasuo; Sakaida, Emiko; Funakoshi, Yasutomo; Moriuchi, Hiroyuki
Abstract: B‐cell expansion with NF‐κB (nuclear factor‐kappa B) and T‐cell anergy (BENTA) is a rare congenital lymphoproliferative disorder caused by germline gain‐of‐function mutations in the CARD11 gene. We herein report a familial case of BENTA due to a G123D heterozygous missense mutation in CARD11 inherited by a male from his mother. The mother's clinical course was characterized by polyarthritis and encephalitis in young adulthood, suggesting that autoimmune‐like manifestations can occur in BENTA. The B‐cell lymphocytosis and splenomegaly seen in her child have been managed with prednisolone and tacrolimus. Further investigations are needed to evaluate the efficacy of calcineurin inhibitors for BENTA.